Implementation of Mathematics through Problem-Based Learning Models Assisted by Numbers Media - Miqwati; Hanafi (Pena Anda: Jurnal Pendidikan Sekolah Dasar, 2024)
Mathematics is a basic science that has a role in shaping students' thinking patterns. In mathematics, students are equipped with various abilities to use logic, systematic, analytical, and critical thinking, as well as to use mathematics in problem-solving. The number bag median makes it easier for students to learn Mathematics. This number bag median is expected to eliminate students' boredom, attention, concentration, and enthusiasm for learning. They are learning research to improve the learning process and student learning outcomes in Mathematics by using the problem beast learning model classroom action research with 2 cycles starting with planning, implementation, observation, and reflection. The results of the first cycle improvement research compared to the initial study experienced an increase of 35.29%. The results of the improvement research in cycle II compared to cycle I experienced an increase of 17.85%. The learning media used is the primary key to the success of the learning process. This is proven based on research results that improving learning can improve student learning outcomes in mathematics learning.